Self-Assembled Pt/MoCx/MWCNTs Nano Catalyst for Ethanol Electrooxidation of Fuel Cells - Cao, Xiaochang; Qiu, Zhongming; Chen, Jianjun; Ai, Tianyu (Frontiers in Chemistry, 2022)
Direct ethanol fuel cells (DEFCs) have attracted more and more attention because of their unique advantages such as low cost and low toxicity. However, sluggish C-C bond cleavage during the ethanol electrooxidation reaction (EOR) in acidic media results in a lower energy yield and gravely hinders the commercialization of DEFCs. Therefore, it is very necessary to develop an anode catalyst with high performance, high stability and low cost to solve this problem. In this paper, Pt/MoCx/MWCNTs nanocomposites with different mass ratios of PtMo were obtained through a molecular self-assembly technology. The structure and morphology of Pt/MoCx/MWCNTs nanocomposites were characterized by several techniques such as XRD, FESEM, XPS etc. The electrochemical performance and stability of Pt/WCx/MWCNTs electrocatalysts toward EOR were investigated in acid electrolytes. The results show that PtMo exists in the form of alloy. The size of Pt/MoCx nanoparticles is very uniform with an average size of ~24 nm. The Pt/MoC0.25/MWCNTs exhibits excellent electrocatalytic activities with an electrochemically active surface area of 37.1 m2 g-1, a peak current density of 610.4 mA mgPt-1 and a steady-state current density of 39.8 mA mgPt-1 after 7200s, suggesting that the Pt/MoC0.25/MWCNTs is a very promising candidate for application in EOR of DEFCs.